2018
DOI: 10.1177/1060028018765187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Vasopressor Discontinuation Strategies in Patients With Septic Shock on Concomitant Norepinephrine and Vasopressin Infusions

Abstract: Among septic shock patients on concomitant NE and VP, discontinuation of VP first was associated with an increased incidence of hypotension; future prospective control trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 21 publications
1
52
1
Order By: Relevance
“…These findings were reproduced by Musallam et al, in which they noted a 7-fold increased risk in hypotension when vasopressin was discontinued first [7]. While the findings of our review did not substantiate these claims, we discovered a longer duration of vasopressor therapy in the cohort of patients in which vasopressin was discontinued first, which may correlate with relative vasopressin deficiency in these patients leading to prolonged hypotension.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These findings were reproduced by Musallam et al, in which they noted a 7-fold increased risk in hypotension when vasopressin was discontinued first [7]. While the findings of our review did not substantiate these claims, we discovered a longer duration of vasopressor therapy in the cohort of patients in which vasopressin was discontinued first, which may correlate with relative vasopressin deficiency in these patients leading to prolonged hypotension.…”
Section: Discussionsupporting
confidence: 68%
“…Patients can continue to experience clinically significant hypotension after vasopressor discontinuation which has been associated with poor outcomes [5][6]. Thus, the optimal approach to discontinuing vasopressors, especially for those patients that required multiple agents has been of question, with several hypotheses that continuing vasopressin therapy and discontinuing norepinephrine first may be beneficial in the likely setting of vasopressin deficiency that can persist for 36 to 96 hours [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…9-11,21,24,28,30 Additional areas with unclear clinical data where cost savings could be realized include initiating vasopressin at a dosage of 0.03 units/min (as opposed to 0.04 units/min) and discontinuing vasopressin prior to norepinephrine. [12][13][14][15][16]31 Although vasopressin up to 0.06 units/min has been used with minimal safety concerns, 24 the seminal trial used 0.03 units/min, 26 which is the guideline-recommended dosage. 1 Evaluations of adjuvant vasopressor strategies for patients in whom norepinephrine monotherapy is inadequate, the discontinuation order of vasoactive medications, and the Those surveyed were asked to indicate their agreement or disagreement with the use of vasopressin for the listed indications for patients with septic shock while considering both available evidence for treatment and cost and while just considering the available evidence.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other initiatives to identify optimal strategies for vasopressin use in septic shock that were evaluated for effects on clinical outcomes have included restriction of vasopressin use in septic shock until the norepinephrine infusion rate is above 50 mcg/min; 9 early, concomitant initiation of norepinephrine and vasopressin; 10,11 and the order of vasopressin discontinuation in resolving septic shock. [12][13][14][15][16] Many of these studies evaluated a small number of clinicians/institutions and failed to evaluate some of the clinical scenarios where vasopressin is often used (eg, severe acidemia, elevated lactate).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a higher incidence of hypotension after vasopressin discontinuation compared with NE discontinuation. [29][30][31][32][33] Patient demographics, vasopressor utilization, and clinical outcomes were similar to the overall cohort (Tables S1 and S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 71%